Role of High-Resolution Image Integration to Visualize Left Phrenic Nerve and Coronary Arteries During Epicardial Ventricular Tachycardia Ablation. (April 2015) - Yamashita, Seigo; Sacher, Frédéric; Mahida, Saagar; Berte, Benjamin; Lim, Han S.; Komatsu, Yuki; Amraoui, Sana; Denis, Arnaud; Derval, Nicolas; Laurent, François; Montaudon, Michel; Hocini, Mélèze; et al.
<x xml:space="preserve">Abstract</x> Background— Epicardial ventricular tachycardia (VT) ablation is associated with risks of coronary artery (CA) and phrenic nerve (PN) injury. We investigated the role of multidetector computed tomography in visualizing CA and PN during VT ablation. Methods and Results— Ninety-five consecutive patients (86 men; age, 57±15) with VT underwent cardiac multidetector computed tomography. The PN detection rate and anatomic variability were analyzed. In 49 patients undergoing epicardial mapping, real-time multidetector computed tomographic integration was used to display CAs/PN locations in 3-dimensional mapping systems. Elimination of local abnormal ventricular activities (LAVAs) was used as ablation end point. The distribution of CAs/PN with respect to LAVA was analyzed and compared between VT etiologies. Multidetector computed tomography detected PN in 81 patients (85%). Epicardial LAVAs were observed in 44 of 49 patients (15 ischemic cardiomyopathy, 15 nonischemic cardiomyopathy, and 14 arrhythmogenic right ventricular cardiomyopathy) with a mean of 35±37 LAVA points/patient. LAVAs were located within 1 cm from CAs and PN in 35 (80%) and 18 (37%) patients, respectively. The prevalence of LAVA adjacent to CAs was higher in nonischemic cardiomyopathy and arrhythmogenic right ventricular cardiomyopathy than in ischemic cardiomyopathy (100% versus 86% versus 53%; P<0.01). The prevalence of LAVAs adjacent to PN was higher in nonischemic cardiomyopathy than in ischemic cardiomyopathy (93% versus 27%; P<0.001). Epicardial ablation was performed in 37 patients (76%). Epicardial LAVAs could not be eliminated because of the proximity to CAs or PN in 8 patients (18%). Conclusions— The epicardial electrophysiological VT substrate is often close to CAs and PN in patients with nonischemic cardiomyopathy. High-resolution image integration is potentially useful to minimize risks of PN and CA injury during epicardial VT ablation.